Metal Ion Complex Compound Fe(III) with Pyrazoline Derivative Ligand as Cd(II) and Zn(II) Heavy Metal Ion Sensor Based on Fluorescence - Yulian Syahputri; Ani Iryani; Linda Jati Kusumawardani; Shinta Safitri (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2022)
The purpose of this research is to synthesize the complex compound of ion Fe3+ with para-di-2-(1-phenyl-3-pyridyl-4,5-dihydro-1H-pyrazole-5-yl)benzene ligand and its potentials as the sensor of Cd2+ and Zn2+ heavy metal ions based on fluorescence. Complex compounds are characterized with a Fourier-Transform Infrared (FTIR) Spectrophotometer, Ultraviolet-Visible (UV-Vis) Spectrophotometer and Spectrofluorometer. Then, a complex compound fluorosensor study is conducted by adding Cd2+ and Zn2+ heavy metal ions using a UV-Vis Spectrophotometer and Spectrofluorometer. The results show that the synthesis of the complex compound formed by reacting Fe metal and pyrazoline derived ligands generates brown precipitate with a yield of 51.25% and a range of melting points of 252.2-253.2 . The result of characterization with FTIR (cm-1) generates 3380.20 (tertiary amine), 2922.31-2852.42 (C-H pyridine), 2360.38 (C=C aromatic), 1595.93-1451.88 (C=N), 1232.25-982.66 (C-N pyrazoline), 751.61-690.29 (C-H aromatic) and 366.54-339.44 (Fe-N). The Uv-Vis spectrophotometer study with a concentration of 5x10-5 M showed two absorption peaks at 246 nm, 354 nm, and 440 nm. The resulting fluorescence intensity of 813.1 a.u. at the wavelenght of 500 nm. The study of complex compound fluorescence shows that the addition of Cd2+ heavy metal ion can be made as fluorosensor with turn-on (enhancement) type, while the complex compound in the addition of Zn2+ heavy metal ion can be made as fluorosensor with turn off-on (quenching-enhancement) type.